Comparison of the Effectiveness of Acupressure and Aromatherapy in Reducing Menstrual Pain in Adolescent Girls - Sofiyati, Sofiyati (International Journal of Nursing and Midwifery Research, 2024)
This research investigates the comparative effectiveness of acupressure and aromatherapy in alleviating menstrual pain among adolescent girls. Menstrual pain, or dysmenorrhea, is a common and often debilitating condition that affects a significant number of young women, prompting the need for accessible and effective non-pharmacological treatment options. A total of 100 adolescent participants experiencing menstrual pain were randomly assigned to two intervention groups: one receiving acupressure treatment and the other using aromatherapy with essential oils. Pain intensity was measured using a visual analog scale (VAS) before and after the interventions. Results indicated that both acupressure and aromatherapy significantly reduced menstrual pain, with the acupressure group showing a greater mean pain reduction of 4.2 points compared to 3.5 points in the aromatherapy group. These findings support the efficacy of both interventions as viable alternatives to traditional pharmacological treatments. The study emphasizes the importance of integrating non-pharmacological approaches into adolescent healthcare to empower young women in managing their menstrual discomfort. Limitations such as small sample size and reliance on self-reported pain measures are acknowledged, highlighting the need for further research to explore the long-term effects and broader applicability of these interventions. Overall, this study contributes to the growing body of evidence advocating for holistic pain management strategies in adolescent health care.